Diagnostic problems that create transit alterations in acute intestinal ischemia - Lucinschi, Alicia; Matteucci, Pablo (Cirugía del Uruguay, 1986)
Authors point out that in a series of 47 patients affected by acule intestinal necrosis, 25% had met a presumptive diagnosis of intestinal occlusion. They discuss the clinical and paraclinical elements to be taken into account to preven! errors in diagnosis and speed the surgical intervention, enabling in that way mesenteric revascularization in time to be effective.